2014
DOI: 10.1039/c3ob41823e
|View full text |Cite
|
Sign up to set email alerts
|

CGmCGCG is a versatile substrate with which to evaluate Tet protein activity

Abstract: Tet family proteins have the ability to convert 5-methylcytosine (mC) to 5-hydroxymethylcytosine, and further to 5-formylcytosine and 5-carboxycytosine. We found that CGmCGCG can be the substrate of Tet protein, and observed iterative oxidation of mC by HPLC analysis. We also demonstrated that Tet protein favours single-stranded DNA over double-stranded DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…Consistently, it has been reported that TET proteins also act on DNA substrates containing six nucleotides. 21 Using a solid phase DNA synthesis technique, we prepared three palindromic DNA sequences 3 , 4 , and 5 each containing 22, 14 and 8 nucleotides, respectively, based on the original 58-mer DNA substrate (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, it has been reported that TET proteins also act on DNA substrates containing six nucleotides. 21 Using a solid phase DNA synthesis technique, we prepared three palindromic DNA sequences 3 , 4 , and 5 each containing 22, 14 and 8 nucleotides, respectively, based on the original 58-mer DNA substrate (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…A number of assays are available to probe for specific bases qualitatively and quantitatively. As noted earlier, Kizaki and Sugiyama reported using 4–6 nt substrates with direct resolution of the reaction products by HPLC (Kizaki & Sugiyama, 2014). However, longer substrates are needed to understand how strand specificity, sequence context, and other factors impact TET activity.…”
Section: Analysis Of Cytosine Modifications In Vitromentioning
confidence: 80%
“…In general, we use DNA oligonucleotides 12–35 nt in length, containing a single TET substrate (mC, hmC, or fC) in a CpG context (although useful HPLC-based assays for substrates as short as 4–6 nt have also been developed; Kizaki & Sugiyama, 2014). TET enzymes exhibit a strong preference for CpGs (Hu et al, 2013) but are thought to be less sensitive to surrounding sequences (Yu et al, 2012).…”
Section: Analysis Of Cytosine Modifications In Vitromentioning
confidence: 99%
“…The binding efficiency of the anti‐hmC monoclonal antibody toward the oligomers was assessed by using hexamer DNA containing either mC or hmC (Figure S1 in the Supporting Information) . The results clearly indicate specificity of the antibody toward hmC, even with short oligomers.…”
Section: Resultsmentioning
confidence: 99%